The Moral Turn in the discourse on interculturality - Busch, Dominic (Glottodidactica, 2018)
Since the start of the new millennium, research into intercultural communication and intercultural competence has embarked on an open debate on normative orientations for action in situations of intercultural contact. The contribution at hand presents the preliminary results and impressions from a thematic qualitative content analysis of central academic publications on intercultural communication from the past six decades. Earlier utilitarian paradigms on the one side and a growing outreach towards interpretative paradigms from ethnographic research have, of late, steered intercultural communication research into a moral vacuum. Since then, the discipline can be characterized as undergoing a moral turn. As a consequence, future research may face an opportunity of reflecting on its own moral paradigms in order to produce even more precise orientations for action in intercultural contacts.